Avaliação de reusabilidade de aplicações web baseadas em frameworks orientados a ações e a componentes: estudo de Caso sobre os Frameworks Apache Struts e JavaServer Faces - Dantas, André Medeiros (2008)
﻿Over the years the use of application frameworks designed for the View and Controller layers of MVC architectural pattern adapted to web applications has become very popular. These frameworks are classified into Actions Oriented and Components Oriented , according to the solution strategy adopted by the tools. The choice of such strategy leads the system architecture design to acquire non-functional characteristics caused by the way the framework influences the developer to implement the system. The components reusability is one of those characteristics and plays a very important role for development activities such as system evolution and maintenance. The work of this dissertation consists to analyze of how the reusability could be influenced by the Web frameworks usage. To accomplish this, small academic management applications were developed using the latest versions of Apache Struts and JavaServer Faces frameworks, the main representatives of Java plataform Web frameworks of. For this assessment was used a software quality model that associates internal attributes, which can be measured objectively, to the characteristics in question. These attributes and metrics defined for the model were based on some work related discussed in the document